STIGMA, INDIVIDUALISM AND ORGANIZATION. MICROPOLITICS IN THE RELATIONS AMONG WOMEN WHO PERFORM COMMERCIAL SEX IN ARGENTINA - Morcillo Pérez, Santiago (2019)
This article addresses the links between women who perform commercial sex, traversed by both solidarity and the competitiveness of the sexual market. Based on in-depth interviews conducted in three cities of Argentina, the analysis ranges from inter-individual relations to broader ones within the framework of political organizations. The links between subaltern and stigmatized women are stressed between recognizing themselves as partners and equals in a “we” or (re) marking a hierarchical difference between the self and the “others”.